Plastid genome sequencing reveals biogeographical structure and extensive population genetic variation in wild populations of Phalaris arundinacea L. in north-western Europe. - HODKINSON, TREVOR (My University, 2017)
New and comprehensive collections of the perennial rhizomatous reed canary grass (Phalaris arundinacea) were made in NW Europe along north-to-south and east-to-west clines from Denmark, Germany, Ireland, Poland, Sweden and the United Kingdom. Rhizome, seed and leaf samples were taken for analysis and genetic resource conservation. A subsample covering the geographical range was characterized using plastid genome sequencing and SNP discovery generated using a long-read PCR and MiSeq sequencing approach. Samples were also subject to flow cytometry and all found to be tetraploid. New sequences were assembled against a Lolium perenne (perennial ryegrass) reference genome, and an average of approximately 60% of each genome was aligned (81 064 bp). Genetic variation was high among the 48 sequenced genotypes with a total of 1793 SNPs, equating to 23 SNPs per kbp. SNPs were subject to principal coordinate and Structure analyses to detect population genetic groupings and to examine phylogeographical pattern. Results indicate substantial genetic variation and population genetic structuring of this allogamous species at a broad geographical scale in NW Europe with plastid genetic diversity organized more across an east-to-west than a north-to-south cline.
PUBLISHED
Keywords: Lolium perenne (perennial ryegrass) reference genome; Lolium perenne (perennial ryegrass) reference genome; Genes & Society; Smart & Sustainable Planet